Pengembangan Emotional Spiritual Quontiont (ESQ) Siswa Melalui Pembelajaran Kitab Safinatun Najah - Afifah, Afifah; Sayidana Salsabillah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
Abstract Humans are God's creatures who are gifted with reason, so education is needed to be able to form characters that can bring goodness in life in the world and in the hereafter. There are many efforts that we can do in the world of education for students to be able to optimize the development of their emotional spiritual quotient (esq). Efforts made in developing students' emotional spiritual quotient (esq) with religious activities carried out daily, weekly and annually by implementing book learning. The book chosen in developing students' emotional spiritual quotient (esq) is the book Safinatun Najah. The researcher intends to reveal how students' emotional spiritual quotient (esq) is developed, how the book Safinatun Najah is learned, and what are the supporting and inhibiting factors in developing students' emotional spiritual quotient (esq) through learning the Book Safinatun Najah. Therefore, the researcher has three objectives, namely to find out how the development of students' emotional spiritual quotient (esq), to find out how the learning of the Safinatun Najah book is, and to find out what the supporting and inhibiting factors are in the development of students' emotional spiritual quotient (esq) through learning the Safinatun Najah Book. The method used in this study is a descriptive method, while the data collection technique in this study uses library research. Keywords: Emotional Spiritual Quotient (ESQ), Kitab Safinatun Najah